2012
DOI: 10.4278/ajhp.110113-quan-22
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Industry-Based Dissemination of an Occupational Sun Protection Program with Theory-Based Strategies Employing Personal Contact

Abstract: Purpose Industry-based strategies for dissemination of an evidence-based occupational sun protection program, Go Sun Smart (GSS), were tested. Design Two dissemination strategies were compared in a randomized trial in 2004 – 2007. Setting The North American ski industry. Subjects Ski areas in the United States and Canada (n=69) and their senior managers (n=469). Intervention Employers received GSS through a Basic Dissemination Strategy (BDS) from the industry’s professional association which included c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 51 publications
2
39
0
Order By: Relevance
“…Prior to the warm-weather season, research staff met with managers to plan for implementation, using a previously-developed protocol based on diffusion of innovations theory. (Buller et al, 2012) Researchers followed up with managers to provide ongoing support for implementation.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the warm-weather season, research staff met with managers to plan for implementation, using a previously-developed protocol based on diffusion of innovations theory. (Buller et al, 2012) Researchers followed up with managers to provide ongoing support for implementation.…”
Section: Methodsmentioning
confidence: 99%
“…As has been reported by others, workplace management plays a vital role in creating a healthy work environment and motivating workers to participate in sun protection practices. 32,33 Other studies have reported increased sunscreen use in association with a supportive workplace culture [34][35][36] ;…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…It appears that both industry distribution in BDS and the added efforts by our project in the EDS did not produce enough implementation to reach guests, despite a higher mean number of GSS materials used in the EDS ski areas. (Authors, 2012). Several factors may explain this failure.…”
Section: Discussionmentioning
confidence: 99%
“…Guests spend far less time at a ski area than employees and thus have fewer chances to be exposed to the GSS communication. In fact, analyses on employees reported elsewhere found that reported message exposure began to increase after just four GSS items were used anywhere in the ski areas, although it was only with high program use (9 or more items) that employee sun protection increased (Authors, 2012). By contrast, guest exposure did not increase until ski areas displayed six GSS items in guest-accessible areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation